Faktor-Faktor Yang Berhubungan Dengan Perilaku Tidak Aman Pada Pekerja Konstruksi Proyek Pembangunan Apartemen PT. X Di Jakarta Timur Tahun 2021 - Iffana Dini Amelia, (2021)
Most work accidents are caused by unsafe behavior by 88%. Unsafe behavior occurs due to predisposing factors such as knowledge and perception, enabling factors such as OSH training and the availability of PPE, and driving factors such as supervision. The construction industry is the most dangerous industry in history. The purpose of this study was to determine the factors associated with unsafe behavior in construction workers at the PT. X in East Jakarta. The method used is observational quantitative with a cross-sectional research design. The sampling technique used accidental sampling with a total sample of 100 workers. The research instrument used observation sheets and questionnaires. The data analysis was used in univariate and bivariate analysis with chi-square. The results showed that there was a significant relationship between knowledge of K3 (p=0.000), K3 training (p=0.038), supervision (p=0.042), and unsafe behavior. Therefore, the company is expected to increase the activities of safety morning talk, toolbox meeting, and safety induction, conduct OSH training and improve routine and strict supervision.